Prediktor Perilaku Merokok Pada Pengguna Rokok Elektrik Ditinjau Dari Health Belief Model: Sebuah Studi Literatur - Wardah Wuri Aisyati; Kesuma Dewi , Triana (Jurnal Syntax Fusion, 2023)
The development of the times has influenced changes in the pattern of life in society. One of them is smoking behavior which is no longer considered a taboo by some people. In Indonesia, e-cigarette users continue to increase every year. E-cigarette enthusiasts are not only men, but many women are also interested in consuming e-cigarettes. Even some of them are new users and decide to become active smokers. The prevalence of female e-cigarette users in Indonesia in 2018 reached 2.7% of users. One model and theory of healthy behavior that can describe an individual's belief in a behavior, especially in the context of this study, namely smoking behavior in women who use e-cigarettes is the health belief model (HBM). Therefore, the author would like to conduct a narrative review of the literature before conducting further research.